Deep habits: Workshop as critique in creative writing. (July 2017) - Stukenberg, Jill
The creative writing workshop, involving peer critique of manuscripts in progress, is deeply connected to many writerly habits of mind. As such, this article examines workshop as a signature pedagogy in creative writing. Through workshop, students develop awareness of their readers, understanding of how texts are created by readers and through process, and abilities to problem-solve in drafts and hone their personal tastes while encountering contemporary aesthetic values. At the same time, examination of the writerly habits of mind transmitted through workshop also reveals other key skills and ways of thinking that can be shortchanged when workshop is too much the sole methodology; one deleterious habit of mind, that of being overly self-critical, may even result.